2021
DOI: 10.1080/08820139.2021.1914081
|View full text |Cite
|
Sign up to set email alerts
|

A Variant of IL1B Is Associated with the Risk and Blood Lipid Levels of Myocardial Infarction in Eastern Chinese Individuals

Abstract: Odds ratios (OR), 95% CI and P values were calculated using logistic regression analysis with adjustment for age, BMI, smoking and sex. HDL, high-density lipoprotein; LDL, low-density lipoprotein; TC, total cholesterol; TG, triglyceride. Italics values are statistically significant (P < 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…These genes were subjected to PPI analysis, resulting in the identification of 10 hub genes. The hub genes identified were IL1B, ZAP70, LCK, FASLG, CD4, LRP1, CDH2, MERTK, APOE and VTN and IL1B was the crucial genes among them.IL‐1B is a key pro‐inflammatory cytokine that is associated with the development of atherosclerosis and MI 23 . IL1B gene polymorphisms affect the risk of MI and ischemic stroke in young adults by modulating the expression of NF‐κB, iNOS, MMP‐2, and Bax 24 .…”
Section: Discussionmentioning
confidence: 99%
“…These genes were subjected to PPI analysis, resulting in the identification of 10 hub genes. The hub genes identified were IL1B, ZAP70, LCK, FASLG, CD4, LRP1, CDH2, MERTK, APOE and VTN and IL1B was the crucial genes among them.IL‐1B is a key pro‐inflammatory cytokine that is associated with the development of atherosclerosis and MI 23 . IL1B gene polymorphisms affect the risk of MI and ischemic stroke in young adults by modulating the expression of NF‐κB, iNOS, MMP‐2, and Bax 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the IL-1β gene, which releases IL-1β as a proinflammatory agent, is associated with cardiovascular diseases, including coronary artery disease, stent restenosis after percutaneous coronary interventions, carotid artery disease, lone atrial fibrillation, and CSFP [42][43][44][45]. In addition, the 315C/T nucleotide transition of the IL-1β gene probably modulates IL-1β protein synthesis and is associated with such cardiovascular diseases as CSFP, coronary artery disease, and myocardial infarction [25,[46][47][48][49]. Previous studies have also indicated the role of genetic predisposing factors in the occurrence of CSFP [22][23][24]50].…”
Section: Discussionmentioning
confidence: 99%
“…From 2016 through 2017, a total of 180 patients with CSFP (49 women [27.2%]) at a median age of 55 (48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62) years were enrolled in the CSFP group. From 2016 through 2018, a total of 87 individuals with normal coronary arteries (56 women [64.4%]) at a median age of 47 (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) years were enrolled in the control group. The baseline and clinical characteristics of both groups are summarized in Table 1.…”
Section: Clinical Characteristics Of the Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, carriers of GA genotype of rs726344 have displayed significantly increased levels of CKMB, total cholesterol, LDLc, HDLc, Troponin I, and triglycerides when compared to individuals with other genotypes, which further increases the risk of MI (Badr EA., et al, 2020). Furthermore, rs1143634 C/T in IL1B is also associated with blood lipid levels, including low-density lipoprotein (LDL) and total cholesterol (TC), in the Eastern Chinese Han population, potentially influencing MI risk (Pan Q., et al, 2021). Conversely, in a population from Western Siberia (Russia), the presence of the G allele of rs708272 has been associated with lower levels of high-density lipoprotein cholesterol and a higher index of atherogenicity, implicating this SNP in the development of MI (Semaev S., et al, 2019).…”
Section: Introductionmentioning
confidence: 99%